Hidden Resilience: Unraveling Women's Vulnerability in Patriarchal Cultural Structures in Sorong City - Lukman Rais; Nanik Purwanti; Dewi Astria Faroek; Mirnawati Kinder; Uswatul Mardliyah (Universitas Muhammadiyah Malang, 2026)
This study aims to analyze the level of patriarchal culture, socio-economic vulnerability, and women's resilience in Sorong City. The research approach used a mixed method and convergent design. The sampling technique used was area sampling and purposive sampling. The research sample consisted of 348 women spread across 41 sub-districts in Sorong City and 5 key informants consisting of government officials, religious leaders, traditional leaders, and women's leaders. Data collection was carried out through surveys, in-depth interviews, and documentation studies. Data analysis through descriptive and thematic statistics will be integrated to draw conclusions. The results of the study found a strong level of patriarchal culture and socio-economic vulnerability due to family disharmony and violence faced by women. Women's resilience e it is supported by optimism, cultural values, and access to protection services. Women's resilience is formed from internal motivation and spirituality to survive due to the stimulus of family continuity. Research has found that the most effective form of resilience is hidden resilience, where women's resistance is formed in a non-confrontational way, not fighting directly but developing negotiations so that their resilience can continue sustainably for the future of the family